2020
DOI: 10.48550/arxiv.2009.00524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tensor Relational Algebra for Machine Learning System Design

Abstract: Machine learning (ML) systems have to support various tensor operations. However, such ML systems were largely developed without asking: what are the foundational abstractions necessary for building machine learning systems? We believe that proper computational and implementation abstractions will allow for the construction of self-configuring, declarative ML systems, especially when the goal is to execute tensor operations in a distributed environment, or partitioned across multiple AI accelerators (ASICs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…; (3) Apply the relational algebra operators nested with these UDFs for performing linear algebra computations. Based on the above ideas, tensor relational algebra (TRA) [66] further introduces a set of tensor-oriented relational operations, such as tile, concat, rekey, transform, join, aggregation, selection, etc. We found that most ML workloads can be decomposed into linear algebra operations that are further represented in such TRA.…”
Section: Background and Related Work 21 ML Model Inferences As Queriesmentioning
confidence: 99%
See 4 more Smart Citations
“…; (3) Apply the relational algebra operators nested with these UDFs for performing linear algebra computations. Based on the above ideas, tensor relational algebra (TRA) [66] further introduces a set of tensor-oriented relational operations, such as tile, concat, rekey, transform, join, aggregation, selection, etc. We found that most ML workloads can be decomposed into linear algebra operations that are further represented in such TRA.…”
Section: Background and Related Work 21 ML Model Inferences As Queriesmentioning
confidence: 99%
“…For example, matrix multiplication is a join followed by aggregation [12,66]. The join pairs two blocks from the two tensors if the first block's column index equals the second's row index.…”
Section: Background and Related Work 21 ML Model Inferences As Queriesmentioning
confidence: 99%
See 3 more Smart Citations